1999
DOI: 10.1152/ajpregu.1999.277.3.r607
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE and the kidney: resolution of old problems and new beginnings

Abstract: The protean properties of 20-hydroxyeicosatetraenoic acid (HETE), vasoactivity, mitogenicity, and modulation of transport in key nephron segments, serve as the basis for the essential roles of 20-HETE in the regulation of the renal circulation and electrolyte excretion and as a second messenger for endothelin-1 and mediator of selective renal effects of ANG II. Renal autoregulation and tubular glomerular feedback are mediated by 20-HETE through constriction of preglomerular arterioles, responses that are maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
225
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(236 citation statements)
references
References 78 publications
10
225
0
1
Order By: Relevance
“…It has been shown that both COX and cytochrome P-450 monooxygenase are expressed in the mTAL (6,9,20,24). Therefore, we explored the possibility that the effect of AA was mediated by either COX-dependent or cytochrome P-450-dependent metabolites of AA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that both COX and cytochrome P-450 monooxygenase are expressed in the mTAL (6,9,20,24). Therefore, we explored the possibility that the effect of AA was mediated by either COX-dependent or cytochrome P-450-dependent metabolites of AA.…”
Section: Resultsmentioning
confidence: 99%
“…Eicosanoids have been demonstrated to regulate the transepithelial NaCl transport in the mTAL (1,2,13,15,20). Moreover, a large body of evidence indicates that cytochrome P-450-dependent metabolites of arachidonic acid (AA) play an important role in regulating a variety of ion transporters in the kidney (8,23,27,29).…”
mentioning
confidence: 99%
“…20-HETE production in the kidney may increase blood pressure in rats through at least three mechanisms: i) 20-HETE might constrict the renal artery through inhibition Ca 2+ -activated K + channels in smooth muscle directly, ii) 20-HETE also acts indirectly as a second messenger for ET-1 and iii) it serves as mediator of selective renal effects of angiotensin II [1,[33][34][35][36]. This is supported by the discovery in the unx/salt/DOCA model, which rats that were uni-nephrectonized, given excess salt and treated with DOCA, had increased blood pressure, which increased progressively over the 3-wk study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ABT-treated LE rats, urine flow and free C H2O increased significantly, and urine osmolality fell in BB rats. The diuretic response seen in BB was unexpected, because EETs and 20-HETE are generally thought to inhibit rather than increase tubular reabsorption of sodium and water in the kidney (26,40).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been reported to play an important role in the control of both renal tubular and vascular function (26). EETs are potent endothelial-derived vasodilators in the renal circulation (17,47).…”
mentioning
confidence: 99%